THE CHOICE INTESTINAL STOMY IN ANOREKTAL MALFORMATIONS IN INFANTS - Yuldashev, Muzaffar; Gafurov , Adxam; Toshboev , Sherzod (Medical science of Uzbekistan, 2023)
To date, there is no single conclusion in the literature on the technical and tactical options for the formation of an intestinal stoma in the primary pathology of children, the degree of damage and the case of an established intestinal stoma. There is still controversy about the enteral tension that occurs after the restoration of the integrity of the intestine. Thus, the optimization of indications, the formation of tactical and technical techniques for applying enterocolostomy in newborns and infants, determining the timing of their reconstruction are among the urgent tasks of neonatal surgery.